Zoneamento de aptidão edafoclimática de espécies de bambu com potencial silvicultural produtivo para o Brasil - Santos, Karina Rodrigues (2017)
It is notable that, with the increase of the world population, the demand for several natural wood resources has considerably increased. Thus, it is ever more necessary to use species that present rapid growth, good quality and that can be used as raw matter for different ends. In this context, the bamboo has gained prominence as a viable alternative to supply the demand for such resources. However, researches that favor its use in the forestry sector are still needed. In this work, four species of bamboo, Guadua angustifolia, Guadua chacoensis, Dendrocalamus giganteus and Bambusa vulgaris, are presented with the objective of predicting favorable areas for the better establishment and development of such species in the Brazilian territory, working as a zoning for edaphoclimatic aptitude, which can aid in decision-making. The study was conducted using georeferenced points of occurrence of the species, collected from online herbariums and environmental variables extracted from the WorldClim, MOD16 and SoilGrids databases, widely used for the predictive modeling of species distribution. The Statistica software was used for the correlation and principal component (PCA) statistical analyses. For creating the models, the Maxent software was used, evaluated by the AUC metric. The final maps were elaborated with the aid of the ArcGis software. The results indicated that the Guadua angustifolia, Guadua chacoensis and Bambusa vulgaris species presented extensive area of adaptation possibilities in the Brazilian territory, unlike the Dendrocalamus giganteus species, which showed adaptation in more restricted areas.